All in one meshplasty verses conventional open meshplasty in inguinal hernia in a tertiary care setup - A., Ajay Raja; R., Lakshmana; Dube, Saumitra; Chintada, Govinda Raju; K., Dhinesh (International Surgery Journal, 2021)
Background: Inguinal hernia surgery has continued to evolve historically from tissue repair to the present tension free repair by using mesh. Various tension free mesh repair have been demonstrated throughout the years after lichten stiens tension free meshplasty but inguinodynia continues to be a problem with all hernioplasties. All-in-one mesh hernioplasty showed zero incidence of inguinodynia in 50 patients who underwent this novel procedure. The primary aim of the study was to compare between all in one meshplasty vs conventional open meshplasty in inguinal hernia in tertiary care setup. Methods: Our study was done in SRM Medical college and research center attached to SRM University in Kattankullathur, Chennai for one and half year. It was comparative study between all in one meshplasty verses conventional meshplasty. A sample size of 100 patients was the part of this study, out of which 50 underwent mesh fixation by all in one meshplasty and 50 patients underwent mesh fixation by conventional meshplasty. Results: All-in-one meshplasty can be considered superior to conventional meshplasty in view of incidence of post-op neuralgia, operative time, duration of stay in hospital. Conclusions: All-in-one meshplasty can be considered as a good replacement for conventional hernioplasty in inguinal hernia repair expecting lesser post-operative morbidity and a better quality of life post-operatively.